Adubação verde em Citrus: Influência na porosidade e retenção de água de um latossolo vermelho-escuro do noroeste do estado de São Paulo - Cristina Alves, M. [UNESP]; Barbosa Paulino, H. [UNESP]; Camillo de Carvalho, M. A. [UNESP]; Menezes de Souza, Z. [UNESP] (My University, 2001)
The objective of this research was to study the porosity, bulk density and retention of water of an Oxisol, located in the Northwestern region of Sn̄o Paulo state, Brazil. The soil was cultivated with Citrus sp., to which green manure was applied between rows for three years. Each of six species of green manure crops (Crotalaria juncea L., Mucuna deeringiana Steph. & Bart., Canavalia ensiformis L. DC., Cajanus cajan L., Lablab purpureum L. and Ricinus communis L.) were seeded for three years (1995, 1996 and 1997) between Citrus rows, plus a treatment with a mix of all six species and a control (natural regrowth af vegetation). The experimental design was a randomized complete block design, with four replications for each of the eight treatments. Water retention, microporosity, macroporosity, total porosity and bulk density were analyzed in the beginning (1995) and end (1997) of the experiment, at three depth ranges (0-0.10; 0.10-0.20 and 0.20-0.40m). We concluded that there were statistically significant differences for bulk density, macroporosity, total porosity and retention of water among the different soil depth ranges; there were no significant differences among treatments though.
Water use in Citrus: Effect on porosity in water retention in a Latossolo vermelho-escuro of Northeast of Estado de Sao Paulo
Keywords: Bulk density; Citrus; Green manure; Macroporosity; Soil physical characteristics; Total porosity; bulk density; experimental study; porosity; soil property; water retention; water use; Brazil; Cajanus cajan; Canavalia ensiformis; Crotalaria juncea; Lablab purpureum; Mucuna deeringiana; Ricinus communis